Real-Life Analysis of Efficacy and Safety of Everolimus Plus Exemestane in Hormone Receptor-Positive, Human Epidermal Growth Factor Receptor-2-Negative Metastatic Breast Cancer Patients: A Turkish Oncology Group (TOG) Study. (7th February 2022) - Bilici, Ahmet; Uysal, Mukremin; Menekse, Serkan; Akin, Semih; Yildiz, Fatih; Turan, Merve; Sezgin Goksu, Sema; Beypinar, Ismail; Sakalar, Teoman; Değirmenci, Mustafa; Erdem, Dilek; Basaran, Gul; et al.
Abstract: Purpose: This study evaluated the efficacy and safety of everolimus (EVE) plus exemestane (EXE) in hormone-receptor positive (HR+), human epidermal growth factor receptor-2-negative (HER2−) metastatic breast cancer (MBC) patients in real-life settings. Methods: Overall, 204 HR+, HER2− MBC patients treated with EVE + EXE after progressing following prior endocrine treatment were included. Overall survival (OS) and progression-free survival (PFS) and safety data were analyzed. Results: The objective response rate, median PFS, and median OS were 33.4%, 8.9 months, and 23.4 months, respectively. Multivariate analysis revealed that negative progesterone receptor status was a significant determinant of poor treatment response ( p = 0.035) and PFS ( p = 0.024). The presence of bone-only metastasis was associated with better treatment response ( p = 0.002), PFS ( p < 0.001), and OS ( p = 0.001). Conclusion: We confirmed the favorable efficacy and safety profile of EVE + EXE for HR+, HER − MBC patients.